Bacterial pericarditis presenting as hemorrhagic pericardial effusion in a 6-year-old girl - Saxena Anita; Singh Navneet; Ramakrishnan S; Kothari Shyamsunder (Wolters Kluwer Medknow Publications, 2008)
Hemorrhagic pericardial effusion is known to occur due to tuberculosis, malignancy, uremia or trauma. We present a rare case of a 6 year old girl with bacterial pericarditis who had hemorrhagic pericardial effusion with cardiac tamponade.